1999
DOI: 10.1091/mbc.10.3.771
|View full text |Cite
|
Sign up to set email alerts
|

Gene Knockouts Reveal Separate Functions for Two Cytoplasmic Dyneins inTetrahymena thermophila

Abstract: In many organisms, there are multiple isoforms of cytoplasmic dynein heavy chains, and division of labor among the isoforms would provide a mechanism to regulate dynein function. The targeted disruption of somatic genes in Tetrahymena thermophila presents the opportunity to determine the contributions of individual dynein isoforms in a single cell that expresses multiple dynein heavy chain genes. Substantial portions of two Tetrahymena cytoplasmic dynein heavy chain genes were cloned, and their motor domains w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 73 publications
3
35
1
Order By: Relevance
“…The templates used were prepared from mutant cell lines that had been cultured in the absence of selective agents for more than 2 months. Previous studies, as well as our own observations, have shown that Tetrahymena dynein mutant genotypes that have not been fully assorted to fixation tend to rapidly revert back to wild type in the absence of selective agents (Angus et al, 2001;Lee et al, 1999). No genotypic reversion is observed in this DYH7neo3 mutant cell line.…”
Section: Incorporation and Fixation Of The Gene Disruption Construct supporting
confidence: 62%
See 1 more Smart Citation
“…The templates used were prepared from mutant cell lines that had been cultured in the absence of selective agents for more than 2 months. Previous studies, as well as our own observations, have shown that Tetrahymena dynein mutant genotypes that have not been fully assorted to fixation tend to rapidly revert back to wild type in the absence of selective agents (Angus et al, 2001;Lee et al, 1999). No genotypic reversion is observed in this DYH7neo3 mutant cell line.…”
Section: Incorporation and Fixation Of The Gene Disruption Construct supporting
confidence: 62%
“…Previous studies in which gene disruptions were made in cytoplasmic dyneins of Tetrahymena resulted in a mutant in which the disrupted allele could not be brought to fixation even after prolonged selection in paromomycin (Lee et al, 1999). This incomplete dynein knockout displayed reversion to the wild-type genotype within a span of days if the selective agent was removed from cell culture.…”
Section: Discussionmentioning
confidence: 96%
“…The phagocytosis of Kupffer cells (Watanabe et al, 1988) and macrophage line J774.16 (Horwitz et al, 1981) cells was prevented by Ca 2+ /CaM inhibitors TFP and W7, suggesting that Ca 2+ /CaM signal regulates the phagocytosis of these cells. In Dictyostelium, the Ca 2+ -binding and actin-crosslinking protein, a-actinin, is localized in the phagocytic cup and is thought to be involved in the phagocytosis (Furukawa and Fechheimer, 1994 (Lee et al, 1999). Dynein is a molecular motor that transduces the chemical energy of ATP hydrolysis into mechanical motion along microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Dyh1 may function in the formation of food vacuoles in T. thermophila cells, as well as in Ca 2+ /CaM signaling. Lee et al did not discuss the molecular mechanisms of phagocytosis in detail (Lee et al, 1999), and the relation between Dyh1 and CaM in the vacuole formation is unknown. It is important to elucidate the relation among Dhy1, CaM, and Ca 2+ /CaM-binding proteins in the formation of food vacuoles in T. thermophila.…”
Section: Discussionmentioning
confidence: 99%
“…a different affinity towards certain organelles. With regard to this phenomenon, kinesin (64,65) and dynein (66,67) alternative splice variants were looked at by several groups and found to be involved in a range of different organellar functions. The elucidation of the function of the different MYO5A splice variants in human melanocytes to see which splice variant is involved in melanosome transport is currently being investigated by our group.…”
Section: Alternative Splicing: Making the Motor Complexes Even More Cmentioning
confidence: 99%